THE DEVELOPMENT OF CORPORATE SOCIAL RESPONSIBILITY IN PROMOTING THE SUSTAINABLE DEVELOPMENT OF ENTERPRISES - Din, Badariah Haji; Guangdong, Wu Jinming (CENTRAL ASIA AND THE CAUCASUS, 2021)
Corporate social responsibility can promote the sustainable development of enterprises and is conducive to the healthy development of the national economy and the world economy. Western countries took the lead in formulating guidelines and policies to promote CSR, and then gradually formed relevant international conventions. Although the development of CSR in Asian countries is relatively late, it is rising rapidly. In order to promote the development of CSR in China, the Chinese government has formulated a series of tax incentive policies. This article reviews the development of CSR globally and in China, and highlights that the Chinese government has made strong policy measures to vigorously support the CSR development of Chinese enterprises.